Application of electrical imaging techniques for the investigation of natural dams: an example from the Thulagi Glacier Lake, Nepal - Pant, Surendra Raj; Reynolds, John M. (Journal of Nepal Geological Society, 2000)
The Thulagi Glacier Lake in the Gorkha District of western Nepal was investigated by electrical resistivity tomography (ERT) to delineate buried glacier ice and permafrost zones within the dam. Data were processed using a 2-D inversion program and by finite-difference forward modelling. Interpretation of the processed electrical images indicates that the method can be used for detecting the buried ice and permafrost by virtue of their very high electrical resistivity values (>20,000 Ohm.m and >5.000 Ohm.m, respectively). The resistivity of permafrost seems to be strongly dependent on the material particle size: the finer the particle size the lower is the value of electrical resistivity. Water-saturated glacier sediments have values of electrical resistivity less than 3,000 Ohm.m. The ERT method was useful in mapping of buried glacier ice and permafrost as well as in differentiating other geological materials constituting the dam.